Adsorption behavior and removal mechanism of arsenic on graphene modified by iron–manganese binary oxide (FeMnOx/RGO) from aqueous solutions1. Issue 83 (9th September 2015) - Zhu, Jin; Lou, Zimo; Liu, Yu; Fu, Ruiqi; Baig, Shams Ali; Xu, Xinhua
<x xml:space="preserve">Abstract</x> Graphene has been used as a supporting matrix to disperse FeMnOx due to its huge specific surface area, and the synthesized novel composite adsorbent (FeMnOx/RGO) was employed for arsenic removal.